2015
DOI: 10.7567/jjap.54.112401
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent optical frequency measurements to reduce the dead time uncertainty of frequency link

Abstract: The absolute frequency of the 87 Sr lattice clock transition was evaluated with an uncertainty of 1.1 × 10 −15 using a frequency link to the international atomic time (TAI). The frequency uncertainty of a hydrogen maser used as a transfer oscillator was reduced by homogeneously distributed intermittent measurement over a fiveday grid of TAI. Three sets of four or five days measurements as well as systematic uncertainty of the clock at 8.6 × 10 −17 have resulted in an absolute frequency of 87 Sr 1 S 0 − 3 P 0 c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 39 publications
3
79
0
1
Order By: Relevance
“…The instability of the TOC is dominated by the performance of the interrogation laser [38] through the Dick effect [44]. This instability is lower than achieved in typical single ion clocks [3,13,29,45], and comparable to many high perfromance lattice clocks [11,30,46,47].…”
Section: This Clock Uses the (5smentioning
confidence: 99%
“…The instability of the TOC is dominated by the performance of the interrogation laser [38] through the Dick effect [44]. This instability is lower than achieved in typical single ion clocks [3,13,29,45], and comparable to many high perfromance lattice clocks [11,30,46,47].…”
Section: This Clock Uses the (5smentioning
confidence: 99%
“…The instability of the TOC is dominated by the performance of the interrogation laser [45] through the Dick effect [50]. It is lower than achieved in typical single ion clocks [3,12,31,51], and comparable to many high performance lattice clocks [2,32,[52][53][54][55][56].…”
Section: Selected For a Viewpoint In Physics P H Y S I C A L R E V I mentioning
confidence: 99%
“…As well as the five direct optical frequency ratio measurements already discussed, these included 16 new absolute frequency measurements: one each of the 1S-2S transition in 1 H [18], the optical clock transitions in 171 Yb [19] and 88 Sr + [20] and the ground state hyperfine transition in 87 Rb [21], two each of the E2 [9,14] and E3 [9,15] transitions in 171 Yb + and the reference transition in 40 Ca + [22], and six of the optical clock transition in 87 Sr [23,24,25,26,27,28]. In addition, a correction [29] was submitted to a previously-used absolute frquency measurement of the optical clock transition in 199 Hg [30] and one earlier absolute frequency measurement of the reference transition in 40 Ca + [31] was withdrawn as new data from the same group suggested that the systematic frequency shifts may have been underestimated in this measurement [22].…”
Section: Analysis Of Data Available In September 2015mentioning
confidence: 99%
“…The sole exception was a directly measured optical frequency ratio between the clock transitions in 27 Al + and 199 Hg + [6], which was used to derive a second absolute frequency value for 27 Al + with much lower uncertainty than the directly measured absolute frequency value [7].…”
Section: Introductionmentioning
confidence: 99%